Intrusion of mandibular primary teeth - Vitug, Jocelyn D.
AF, a four year old patient was referred to the Pediatric Dentistry Division by the PCMC-Out Patient Department due to tooth mobility secondary to a fall. She consulted the Out Patient Department a day after the trauma presenting signs of infection.
Keywords: Intrusion; Trauma; Primary teeth